sum+=arr(i,j) * ( (i+1,j+1) * (n-i,m-j))
in this line why are we adding 1 to i and j and subtracting i and j from n and m respectively
sum+=arr(i,j) * ( (i+1,j+1) * (n-i,m-j))
in this line why are we adding 1 to i and j and subtracting i and j from n and m respectively
hi
in this approach our aim is to calculate contribution of each cell
as explained in video how to calculate this
we have to select 2 points top left and bottom right
for top left selected rectangle is from 0,0 to i,j
and no of element in it is length * breadth
length=i+1;
breadth=j+1;
so it is (i+1)(j+1)
similarly for bottom right point selection
length=(n-1 -i +1)=n-i;
breadth=(n-1 -j +1)=n-j
so it is (n-i)(n-j)
i hope this help
if you have more doubts regarding this feel free to ask
if your doubt is resolved mark it as resolved from your doubt section inside your course
for more clearity watch video again